Enhanced efficacy and limited systemic cytokine exposure with membrane-anchored interleukin-12 T-cell therapy in murine tumor models. Issue 1 (19th January 2020) - Zhang, Ling; Davies, John S; Serna, Carylinda; Yu, Zhiya; Restifo, Nicholas P; Rosenberg, Steven A; Morgan, Richard A; Hinrichs, Christian S
Abstract : Background: Interleukin-12 (IL-12) is a potent, proinflammatory cytokine that holds promise for cancer immunotherapy, but its clinical use has been limited by its toxicity. To minimize systemic exposure and potential toxicity while maintaining the beneficial effects of IL-12, we developed a novel IL-12-based therapeutic system that combines tumor-specific T-cell-mediated delivery of IL-12 with membrane-restricted IL-12 localization and inducible IL-12 expression. Methods: Therapeutic T cells targeting a tumor antigen were genetically engineered to express membrane-anchored IL-12 (aIL-12). Expression, function, and shedding of the aIL-12 molecule was assessed in vitro. Tumor treatment efficacy was assessed in vivo with T cell receptor (TCR) transgenic murine tumor models and a tumor xenograft model. Key outcomes were change in tumor size, circulating levels of IL-12 and other cytokines, and survival. Toxicity was assessed via change in body weight. Tumor growth curve measurements were compared using repeated-measures two-way analyses of variance. Results: Retroviral gene transfer resulted in cell membrane expression of aIL-12 by transduced T cells. In each of two transgenic murine tumor models, tumor-specific T cells constitutively expressing aIL-12 demonstrated increased antitumor efficacy, low circulating IL-12 and interferon-γ, and no weight loss. Expression of aIL-12 via a NFAT- inducible promoter resulted in coordinate expression of aIL-12 with T cell activation. In an OT-I TCR transgenic murine tumor model, the NFAT -inducible aIL-12 molecule improved tumor treatment and did not result in detectable levels of IL-12 in serum or in weight loss. In a human tumor xenograft model, the NFAT -inducible aIL-12 molecule improved antitumor responses by human T cells coexpressing a tumor-specific engineered TCR. Serum IL-12 levels were undetectable with the NFAT -inducible construct in both models. Conclusion: Expression of aIL-12 by tumor-targeting therapeutic T cells demonstrated low systemic exposure and improved efficacy. This treatment strategy may have broad applications to cellular therapy with tumor-infiltrating lymphocytes, chimeric antigen receptor T cells, and TCR T cells.